Hubungan Antara Tuhan, Manusia, dan Alam Menurut Pandangann Imam Al-Ghazali dalam Tahafut Al-Falasifah - Ma’lumah, Ulima Dya’ul (Program Studi Aqidah dan Filsafat Islam STISA Ash-Shofa Tasikmalaya, 2025)
This article aims to explore Al-Ghazali's thoughts on the relationship between humans, nature, and God. Therefore, the destruction of nature caused by disharmony between humans, nature, and God has led to major problems resulting in various disasters such as fires, floods, landslides, earthquakes, tsunamis, droughts, and erosion. Modern man's view on the objectification of nature is the issue examined in this article. It is hoped that from this publication we can find the main formulation of Al-Ghazali's thoughts on eco-sufism as an alternative solution to the environmental crisis. The research data comes from al-Ghazali's writings which include human ethics towards God and human ethics towards nature, as well as the relationship between the two. This article presents a qualitative study with a content analysis methodological approach from several of al-Ghazali's works that discuss nature and the environment. From various excavations of al-Ghazali's works, it can be seen that the cause of disharmony in the relationship between nature, humans and God is caused by consumption factors related to the needs of human life, thus making humans greedy and aiming to fulfill their needs in life. Nature is a manifestation of God's love on earth, but loving God must be through God's love for nature. Therefore, establishing an ethical relationship between humans, nature and God requires Uzra, Mahabba, Wala Etika, asceticism and gratitude.